The South China Sea disputes and the U.S.-China contest international law and geopolitics - Hsiung, James C. (Series on contemporary China ;, 2018)
This book focuses on a region that, next to the Middle East, has become a dragnet of international conflicts in the world. The South China Sea (SCS) region, furthermore, is the subject over which a rumored war may break out between the United States, the extant superpower, and China, an emergent superpower -- should the current power transition end up in a Thucydides Trap. The book's final part explores a possible way out of the two tangles, in the interest of arriving at a reconciliation of the tensions and conflicts associated with the SCS, so that the United States and China can meet each other across the divide for the sake of a new era of public order, presumably under a condominium they can build together.